2021
DOI: 10.1021/acs.chemrestox.0c00340
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Family Nanomaterials in Ocular Applications: Physicochemical Properties and Toxicity

Abstract: Graphene family nanomaterials (GFNs) are rapidly emerging for ocular applications due to their outstanding physicochemical properties. Since the eyes are very sensitive organs and the contact between the eyes and GFNs in eye drops, contact lenses, intraocular drug delivery systems and biosensors and even the workers handling these nanomaterials is inevitable, it is necessary to investigate their ocular toxicities and physiological interactions with cells as well as their toxicity mechanisms. The toxicity of GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 148 publications
0
17
0
Order By: Relevance
“…It was estimated that the concentrations of discharged NMs in the surface and effluent waters could reach μg/L levels (Giese et al 2018;Gottschalk et al 2009;Keller and Lazareva 2014). Labscale experiments have showed that NMs could induce oxidative damage or adsorb enzymes to interrupt the metabolic activity of organisms (Borandeh et al 2021;Nguyen et al 2018;Schultz et al 2012). Moreover, NMs could act as carriers to bring heavy metal ions or organic pollutants into organisms (Fan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that the concentrations of discharged NMs in the surface and effluent waters could reach μg/L levels (Giese et al 2018;Gottschalk et al 2009;Keller and Lazareva 2014). Labscale experiments have showed that NMs could induce oxidative damage or adsorb enzymes to interrupt the metabolic activity of organisms (Borandeh et al 2021;Nguyen et al 2018;Schultz et al 2012). Moreover, NMs could act as carriers to bring heavy metal ions or organic pollutants into organisms (Fan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, particles below 35 nm are able to cross the BBB. When graphene enters the cell, there is a potential to cause cell damage; this can perhaps be minimized through functionalization [ 108 ]. In the majority of cases, coating GO with biocompatible polymers helps improve its biocompatibility and reduce its toxicity [ 87 ].…”
Section: Graphene Oxide: Biocompatible or Cytotoxic?mentioning
confidence: 99%
“…Furthermore, an increasing number of research groups devoted their attention to develop alternative MSCs mediated therapies. In this framework, many articles have reported on the combination of various approaches to resolve any resulted synergistic effect on cytotoxicity which remains a major clinical problem in tissue engineering [115,119,121].…”
Section: Graphene Family Combined With Human Mesenchymal Stem Cellsmentioning
confidence: 99%